(untitled) (Interdisciplinary Studies Journal, 2025)
he study proposes the development of the concept of the bisector of an internal angle of any triangle by a group of eighth-grade students in a school located in the Semi-Arid region of Potiguar, using the Interactive Didactic Sequence (ITS) as a pedagogical approach. The responses derived from the students’ preexisting knowledge were reviewed and condensed into sets to derive a definition to be debated, using the GeoGebra Learning Object as a teaching resource. GeoGebra proved to be an interactive software that facilitates learning. Regarding the concept under study, the presented conceptual maps demonstrated that the students improved their knowledge in a conversational and interactive manner. The conclusions reveal that the IDS approach fosters interactive discussions, enabling the construction of knowledge based on the students’ prior understanding.